Вплив нового похідного L-лізину на показники окислювального стресу та розвиток неврологічного дефіциту у тварин з гострим порушенням мозкового кровообігу - Бєленічев, Ігор Федорович; Єгоров, Артем Анатолійович; Мазур, Іван Антонович; Belenichev, I. F.; Egorov, A. A.; Mazur, I. A.; Беленичев, И. Ф.; Егоров, А. А.; Мазур, И. А. (My University, 2010)
В статье представлены результаты влияния нового производного L-лизина на показатели окислительного стресса и развитие неврологического дефицита у подопытных животных (крыс) при моделировании острого нарушения мозгового кровообращения, путем двусторонней перевязки сонных артерий. There are presented in the article the results of influence of new derivative of L-lysine on the indexes of oxidative stress and development of neurologic deficit in experimental animals (rats) at simulation of the acute violation of cerebral blood circulation by the bilateral bandaging of carotids.
Researches for influence of the new derivative of L-lysine on the indexes of oxidizing stress and development of neurological deficiency in animals with acute violation of cerebral blood circulation
Влияние нового производного L-лизина на показатели окислительного стресса и развитие неврологического дефицита у животных с острым нарушением мозгового кровообращения
Keywords: гостре порушення мозкового кровообігу; L-лізин; нейропротекція; антиоксидантна активність; acute violation of cerebral blood circulatio; L-lysine; neuroprotection; antioxydative activity